Productive performance and qualitative egg characteristics of two local lines chickens and laying brown Lohmann - Tawfeq, Esraa Mobasher; Al-Neemy, Majid Ahmed Sabri (Journal of agricultural, environmental and veterinary sciences, 2022)
This study was conducted to compare the productive performance of two local lines chickens (black and brown- feathered chickens) and laying brown Lohmann strain for the period from 4- 6 months of age. The birds were divided into three treatments, the first treatment Local black, the second local brown, and the third brown Lohmann, with 15 females and 3 males from each group divided into three replicates (1 ♂: 5 ♀). The following characteristics were studied: live body weight, age of sexual maturity, weight of the first egg, average weight of eggs, egg production % HD, egg mass, feed conversion ratio and egg specific characteristics for the three groups. The results indicated that there were significant differences (P < 0.05) in the characteristic of live body weight at sexual maturity and at 6 months of age in favor of brown Lohmann, which was 1207.2, 1032.1, 1109. 7 g and 1379.6, 1207.4, 1219.8 for the Lohmann brown chicken, local brown chicken and black local chicken. Also, the brown Lohmann chickens showed the lowest age of sexual maturity of 138.13 days, which was significantly (P < 0.05) superior to the local brown chickens' 143.00 days, which in turn was significantly superior to the black local chickens 148.33 days. The black local chickens achieved a significant (P
Keywords: local breeds; Lohmann brown laying; egg production; egg quality characteristics